KEKUATAN HUKUM BADAN HUKUM YANG BERBENTUK KOPERASI DALAM MENGAJUKAN PERMOHONAN KEPAILITAN - Widy Asshidiq, Abdullah; Yustisio, Rifki; Miftahzen Reza, M. Hilmi (Realism: Law Review, 2023)
This study aims to determine the legal position of the bankruptcy filing application for business entities in the form of cooperatives. This research is normative-juridical research using a conceptual approach method. The data used are primary, secondary and tertiary data. The results of this study will focus on the mechanism of filing a bankruptcy application by the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia (Kemenkop) against cooperatives in Indonesia according to Supreme Court Circular Letter No. 1 of 2022. The results of the study concluded that based on the provisions of the Supreme Court Circular Letter SEMA Number 1 of 2022 concerning Special Civil Procedures governing PKPU and Bankruptcy Mechanisms, explaining that Cooperatives can no longer be filed PKPU and Bankruptcy directly but related to the application for bankruptcy filing against cooperative bankruptcy filings can only be done by the Ministry of Cooperatives